Forest fire disasters and ecological crisis: Impacts on women - Anastasia, Ayu; Nabilla, Fitria (ASEAN Natural Disaster Mitigation and Education Journal, 2025)
Background: Forest and land fires in Riau Province are a recurring issue with significant consequences for the economy, society, and environment. This research examines the impacts of these fires and explores the role of women in disaster mitigation efforts. Method: The research used a Desk Study method, collecting secondary data from government reports, scientific journals, and previous studies to conduct a descriptive analysis. Findings: The fires result in substantial material losses, including damage to natural habitats, loss of commercial timber, extinction of local wildlife, and health issues for local communities, with women experiencing disproportionate impacts. However, women also have considerable potential as agents of change in disaster mitigation. Their involvement in sustainable natural resource management and policy-making processes can enhance community resilience to forest and land fires. Conclusion: Involving women in disaster mitigation efforts, particularly in sustainable resource management and policy-making, can lead to more effective and holistic strategies for managing forest and land fires. Novelty/Originality of this article: This study provides new insights into the importance of gender inclusion in disaster risk reduction, emphasizing the potential for women's active participation in mitigating the impacts of forest and land fires in Riau Province.